(untitled) (Annals of Medical Research, 2021)
Aim: The aim of the present study was to evaluate serum levels of S-100B which is an acidic calcium-binding protein within the first 36 hours following an acute ischemic stroke and to determine the correlation between S-100B levels and National Institutes of Health Stroke Scale (NIHSS) scores. Material and Methods: Fifty patients with ischemic stroke (25 male, 25 female; mean age=64) and 30 healthy volunteers (14 male, 16 female; mean age=61) serving as age and sex matched controls were included in this study. Venous blood samples were taken within the first 36 hours following the acute stroke. The quantitative determination of S-100B in serum was carried out using an enzyme linked immunosorbent assay.Results: Patients with acute ischemic stroke had significantly higher serum S-100B protein concentrations (42 pg/ml) than those of normal controls (31.5 pg/ml) (p0.001). S-100B concentrations were correlated with NIHSS scores (r=0.443; p=0.001), which is considered an indicator of the degree of neurological deficit.Conclusion: The present study demonstrates that S-100B concentrations in both the large artery atherosclerosis (LAA), cardio embolic infarct (CEI) subtypes of acute stroke are increased in the early phases of stroke and are correlated with NIHSS scores upon admission. S-100B appears to be a valuable biomarker of ongoing brain injury.